Environmental Health and Safety: Social Aspects - Bertolatti, Dean; Hannelly, Toni; Jansz, Janis (Elsevier, 2015)
Abstract Environmental health factors play a significant role in human health and the protection of the environment. The health impacts resulting from exposure to these factors are closely linked to social aspects such as socioeconomic status and access to health care. Three current environmental case studies are discussed from both an environmental and a social aspect.